Spatial variability of selected soil properties and its impact on the grain yield of oats (Avena sativa L.) in small fields. (26th November 2018) - Hausherr Lüder, Ruth-Maria; Qin, Ruijun; Richner, Walter; Stamp, Peter; Noulas, Christos
Abstract: To investigate spatial variability in topsoil (0–20 cm) pH, available phosphorus (P), potassium (K), total nitrogen (N), and soil organic matter (SOM) of small fields (∼2 ha), and to determine the impact of soil heterogeneity on the spatial variability of crop yield two fields were cropped with spring oats and one with winter wheat under humid-temperate conditions. In the two oat fields, some of the measured soil properties (P, K) and the grain yield varied considerably, and strong spatial trends were recorded for most of the soil traits. In the third field, soil properties showed only a moderate spatial variation, and no spatial trends were found. The spatial distribution of SOM and total N in the topsoil had some influence on the spatial pattern of the oat grain yield in the field of Gränichen; however, spatial relationships between soil chemical properties and grain yield were rather weak in our study.